Art as ritual engagement in the funerary programme of Watetkhethor at Saqqara, c. 2345 BC - O'Neill, Barbara (Egyptologist) (Access archaeology., 2023)
Art as ritual engagement is examined through a case study of feminised funerary representation in the repertoire of Watetkhethor, an elite woman interred in the mastaba tomb of her spouse, Mereruka, at Saqqara, c.2345-2181 BCE.